KONSEP MᾹQᾹṢID AL-SYᾹRĪAH MENURUT ṬᾹHᾹ JᾹBIR AL-‘ALWᾹNĪ - Najidah, Chasnak (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2016)
One discourse which is receiving considerable attention from scholars of Islam is about the objectives of Islamic law (maqasid al-shari'ah). Taha Jabir al-'Alwānī as one reviewer of Maqasid al-shari'ah contemporary formulate the concept of maqasid al-shari'ah different from previous scholars. This article describes the concept of maqasid al-shari'ah by Taha Jabir al-'Alwānī. According to him, there are three levels of hierarchical of Maqasid al-Sharia. The highest value of maqasid al-shari'ah says is what he describes as al-Maqasid al-'ulyā al-Hakimah (intentions of the highest shari'ah and a legal basis), which consists of three main elements, namely al-Tawhid ( Onesess of God), al-Tazkiyah (purification) and al-'umrān (prosperity). The position of the second al-shari'ah Maqasid are universal values such as justice, freedom, and equality. While the third position is the formulation of the previous scholars regarding maqasid al-shari'ah consisting of ḍarūriyyat, ḥājiyyāt, and taḥsīniyyāt. In terms of methodological, Taha Jabir al-'Alwānī basing the new system for Maqasid al-syarī'ahnya on the methods of al-jam'u Baina al-qirā'atain, a reading of the two entities: the revelation of God and the universe. With this basis, he argues that the maqasid al-shari'ah formulations are qaṭ'ī, so it can be a reference to the scholars in solving the problems of contemporary law. [Salah satu diskursus yang mendapat perhatian cukup besar dari para akademisi Islam adalah seputar tujuan-tujuan hukum islam  (maqāṣid al-syarī'ah). Ṭāhā Jābir al-‘Alwānī sebagai salah satu ulama pengkaji maqāṣid asy-syarī’ahkontemporer merumuskan konsep maqāṣid asy-syarī’ahyang berbeda dari ulama sebelumnya. Artikel ini mendeskripsikan konsep maqāṣid asy-syarī’ahmenurut Ṭāhā Jābir al-‘Alwānī. Menurutnya, ada tiga tingkatan hierarkis maqāṣid al-syarī'ah. Nilai tertinggi maqāṣid asy-syarī’ahmenurutnya adalah apa yang disebutnya sebagai al-maqāṣid al-‘ulyā al-ḥākimah (maksud-maksud syari’at yang tertinggi dan menjadi landasan hukum) yang terdiri dari tiga unsur pokok, yaitu al-tauḥīd (pengesaan Allah), al-tazkiyah (penyucian) dan al-‘umrān (pemakmuran). Posisi maqāṣid asy-syarī’ah kedua yaitu nilai-nilai universal seperti keadilan, kebebasan, dan persamaan. Sementara posisi ketiga adalah rumusan ulama terdahulu mengenai maqāṣid asy-syarī’ahyang terdiri dari ḍarūriyyat, ḥājiyyāt, dan taḥsīniyyāt. Dari segi metodologis, Ṭāhā Jābir al-‘Alwānī mendasarkan sistem baru maqāṣid al-syarī'ahnya pada metode al-jam’u baina al-qirā’atain, yaitu sebuah pembacaan terhadap dua entitas: wahyu Allah dan alam semesta. Dengan dasar inilah, ia berpendapat bahwa maqāṣid asy-syarī’ahrumusannya bersifat qaṭ’ī, sehingga dapat menjadi rujukan para ulama dalam menyelesaikan problematika hukum kontemporer.]